Persistence of Congenital Mirror Movements after Hemiplegic Stroke - Rocca, Maria A. (AJNR Am J Neuroradiol, 2005)
Summary: We describe a case of hereditary congenital mirror movements (MMs) in a 76-year-old man, who after an ischemic stroke, had persistence of MMs in the paretic hand during voluntary movements of the contralateral arm. By using functional MR imaging to investigate the performance of motor and sensory tasks with the affected and the unaffected hands, we found evidence for increased ipsilateral primary motor cortex activity and reduced transcallosal inhibition. Both these mechanisms are likely to be involved in the genesis of MMs.